GLOBAL PACT FOR THE ENVIRONMENT: ELEMENTS OF CODIFICATION OR/AND A NEW INTERNATIONAL AGREEMENT - Todić, Dragoljub C (Zbornik radova Pravnog fakulteta u Nišu, 2023)
The paper explores the relationship between the Draft Global Pact for the Environment (Global Pact) and relevant international documents (declarations and international environmental agreements) and the Republic of Serbia (RS) legislation. The first part of the article provides a survey of the contents of the Global Pact pointing to the significance of the international environmental law principles (principles) this document includes. The part of the paper deals with the relationship between the Global Pact principles and RS legislation. The relationship between the Global Pact and right to a (healthy) environment is particularly stressed. The author concludes that the norms of the Global Pact and those of the international environmental agreements, and RS domestic laws coincide to a great extent. Apart from the intentions to codify environmental law principles the Global Pact also introduces some new principles whose contents and scope should be analysed in detail.